Development of degradable biofilms from breadfruit (Artocarpus altilis) flour as an alternative to the use of conventional synthetic plastics. - Moreno Toasa, Gabriel Alejandro; Galarza Sanabria, Inés Abigail; Sailema Ortiz, Magdalena Lizbeth (Tierra Infinita, 2024)
This work analyzes the environmental problems derived from the use of conventional synthetic plastics, which, due to their resistance and long useful life, generate waste accumulation and health problems associated with the ingestion of microplastics and the release of toxic substances. As a sustainable alternative, the development of biodegradable biofilms from breadfruit flour (Artocarpus altilis) is proposed. The objective of the research is to evaluate the viability of these biofilms as an ecological substitute for petroleum-derived plastics, by characterizing their physical, mechanical and optical properties, as well as their degradation capacity under controlled soil conditions. The methodology included obtaining biofilms from starch present in breadfruit flour, followed by tests to determine their properties and biodegradability rate. The biofilms prepared in the laboratory were subjected to controlled degradation conditions in soil. The results indicated that these biofilms presented good physical, mechanical and optical properties suitable for use as an alternative material to synthetic plastics, with a capacity for complete degradation in approximately 30 days. In conclusion, it was demonstrated that biofilms based on breadfruit flour are a viable and ecological solution to reduce environmental pollution caused by conventional plastics, contributing to the sustainability of the environment.
Keywords: Biofilms; Degradation; Breadfruit; Starch; Bioplastic